Duration of an acute moderate-intensity exercise session affects approach bias toward high-calorie food among individuals with obesity. (1st May 2022) - Li, Yansong; Xia, Xue; Yu, Anqi; Xu, Huangmei; Zhang, Chunhua
Abstract: Obesity is partly driven by unhealthy eating behaviors underpinned by an approach bias toward high-calorie food. Although exercise is a useful strategy for weight loss among individuals with obesity, whether exercise modulates this approach bias is unclear. This study assessed whether the duration of an acute moderate-intensity exercise altered the approach bias toward high-calorie food among individuals with obesity. In total, 24 individuals with obesity were included in this study with a randomized, counterbalanced, crossover design. Participants completed three sessions of 30, 45, or 60 min of moderate-intensity exercise (40%–59% of heart rate reserve) on an elliptical trainer or completed a control rest session for 55 min. Food approach bias was evaluated using a joystick-based approach-avoidance task immediately before and after each session. Two-way repeated-measures analysis of variance was used to analyze the data. We found that compared with that before exercise, the approach bias score toward high-calorie food was significantly decreased only in the 45-min exercise session ( p = .015) and that this score was also significantly lower than that after both the 60-min exercise session ( p = .002) and the control session ( p = .024). These findings suggest a dose-response relationship between exercise duration and approach bias, with 45 min of moderate-intensity exercise being an effective strategy for decreasing the approach bias toward high-calorie food among individuals with obesity.